Frozen Dice Enterprise / Nur Adilah Zulkiply… [et al.] - Zulkiply, Nur Adilah; Abd Razak, Nur Farah Hanim; Asari, Amir Syukri; Norazlan, Nurul Syafiqah (2010)
FROZEN DICE is a special name creates by us to show our personality. Two simple words that will bring changes to the frozen food retail industry. In the same time, we bring the uniqueness and creativity into this industry. Frozen is refer to our product which is typical and assorted frozen food. Dice is refers to all product and future product from our company in dice or square shape. This is the originality of our company. We come with our own identity which is SQUARE. Besides focus on taste of our product, we really stress on our identity which is dice or square. The originality of our products is among the main things that need to focus in producing area. Our emphasis will be on producing, making and selling chicken square. Frozen Dice will be an outlet that can help our target customer to make their life more easier. Such as working parents and food sellers which will easily attract to our product that really have different shape and really easy to prepared. Besides, it also can give new experience when eating with food that comes with new shapes. As everyone knew, George Town already declared as UNESCO World Heritage Site, it much and more gives some advantage for us to distribute and start a new product in Penang area. We hope to run our business on 15th January 2011. Our company is formed among 4 partners that share the same dream and vision in developing and being part of the frozen food industry in Malaysia, all of whom will be invaluable to the new venture. Our outlet will be located at: Lot 103, Persiaran Perda 15, Bandar Perda, 13500 Permatang Pauh, Pulau Pinang. We choose this location because the turn over people in and out from this area is high. So to expand a new company it is a benefit for us. So that, we satisfied and agree to start up our business in Bandar Perda.